2021
DOI: 10.1021/acs.jpca.1c06166
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Analysis of the Transient Absorption Spectrum of 4-(N,N-Dimethylamino)benzonitrile (DMABN) in Acetonitrile

Abstract: 4-( N , N -Dimethylamino)benzonitrile (DMABN) is a well-known model compound for dual fluorescence—in sufficiently polar solvents, it exhibits two distinct fluorescence emission bands. The interpretation of its transient absorption (TA) spectrum in the visible range is the subject of a long-standing controversy. In the present study, we resolve this issue by calculating the TA spectrum on the basis of nonadiabatic molecular dynamics simulations. An unambiguous assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 84 publications
1
18
0
Order By: Relevance
“…The decay rates we obtain in our direct dynamics simulations are very similar to those in [ 35 , 36 , 65 ], in which TDDFT was also used for the electronic structure. A very similar decay rate is also observed in ADC2 in the gas phase, water and acetonitrile in [ 33 , 34 , 64 ]. The authors concluded that the solvent environment does not affect the initial internal conversion.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The decay rates we obtain in our direct dynamics simulations are very similar to those in [ 35 , 36 , 65 ], in which TDDFT was also used for the electronic structure. A very similar decay rate is also observed in ADC2 in the gas phase, water and acetonitrile in [ 33 , 34 , 64 ]. The authors concluded that the solvent environment does not affect the initial internal conversion.…”
Section: Resultssupporting
confidence: 67%
“…In a later publication in 2020, Kochman and Durbeej improved the previous setup using QM/MM on DMABN in a water nanodroplet, and observed for the first time the formation of the TICT state at around 600 fs. Very recently, they have applied the CC2 method to compute the transient absorption spectra of DMABN in acetonitrile [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…85 However TSH at algebraic diagrammatic construction method showed an almost complete depopulation of S 2 , without back hops to that state. 31 Along our simulation time, we can clearly see the oscillations typical of this behavior in the population profiles, until the S 2 population is 20% of the total one after 100 fs.…”
Section: Dmabn Non-adiabatic Dynamicsmentioning
confidence: 68%
“…The TA spectrum of DMABN has been studied both experimentally and computationally, 31,74 and helps understanding the ultrafast dynamics of the molecule and the role of the two states involved in the fluorescence of the system. The early spectrum, in the first 100 fs, is composed in the 1-6 eV energy range by two main contributions.…”
Section: Dmabn Transient Absorptium Spectrummentioning
confidence: 99%
See 1 more Smart Citation